The impact of the Covid-19 lockdown on consumer access to organic food in San José, Costa Rica (UNED Research Journal, 2021)
Introduction: The Covid-19 pandemic has led to increased awareness of food security in urban areas and to the role of farmers’ markets in providing essential services to consumers. Objective: To better understand how Covid-19 affected consumer access to organic food at two major organic farmers’ markets in the Costa Rican metropolitan area. Methods: In April 2020 after the strict Costa Rica lockdown, 52 organic market consumers completed online questionnaires regarding their purchasing and consumption patterns. Results: The majority of participants reported decreasing or stopping visits to organic markets (81%). The most frequent source of food during the pandemic was large supermarkets (52%) followed by online or direct delivery from farmers (15%). The majority of participants reported less access to organic products since the onset of the pandemic (71%). Conclusion: Covid-19 has impacted access to organic food at farmer’s markets; recommendations include greater support for direct and online delivery of organic products to increase access to health food.
Keywords: Food security; Farmers markets; Smallholders; Agroecology; Pandemic; Organic agriculture